PENGARUH KOMPETENSI GURU TERHADAP HASIL BELAJAR IPS SMP DI KABUPATEN BENGKAYANG - Kutis, K.; Mashudi, Mashudi; Matsum, Junaidi H. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purposes of this study are (1) to explain the competence degree of Social Science teacher in SMP et Kabupaten Bengkayang, (2) to explain how far the effect of teacher competences partially, those are pedagogy, personal, social, and professional towards the student achievements of SMP Se-Kabupaten Bengkayang  , (3) to explain the effect of teacher competence towards the student achievements of SMP se Kabupaten Bengkayang. The approach used of this study is qua ntitative approach witj correlational method that aims to figure out the correlation and closenees of two correlations. The data used is the result of regression analysis which will be simulated. The result of this study are (1) According to the distributed data, the degree of teacher competence in SMP et Kabupaten Bengkayang is sufficient with percentage of pedagogy competence is 45,5%, 37,6% personal competence, 32,4% social competence, and 32,4% professional competence. (2) The data showspartial positive between teacher competence towards the achievement students, those are pedagogy competence t count = 2,791 and significant 0,05 ; personal competence t count = 3,067 and significant 0,05; social competence t count=3,067 significant 0,05; and professional competence t count=2,848 amd significant 0,05.  Keyword: Pedagogy Competence, Personal Competence, Social Competence, Professional Competence and The Student Achievement